Genetic Biopsy for Prediction of Surveillance Intervals after Endoscopic Resection of Colonic Polyps: Results of the GENESIS Study. Issue 2 (1st March 2018) - Berger, Andreas W; Raedler, Katja; Langner, Cord; Ludwig, Leopold; Dikopoulos, Nektarios; Becker, Karl F; Slotta‐Huspenina, Julia; Quante, Michael; Schwerdel, Daniel; Perkhofer, Lukas; Kleger, Alexander; Zizer, Eugen; et al.
Abstract : Background and objective: Current surveillance strategies for colorectal cancer following polypectomy are determined by endoscopic and histopathological factors. Such a distinction has been challenged. The present study was designed to identify molecular parameters in colonic polyps potentially defining new sub‐groups at risk. Methods: One hundred patients were enrolled in this multicentre study. Polyps biopsies underwent formalin‐free processing (PAXgene, PreAnalytiX) and targeted next generation sequencing (38 genes (QIAGEN), NextSeq 500 platform (Illumina)). Genetic and histopathological analyses were done blinded to other data. Results: In 100 patients, 224 polyps were removed. Significant associations of genetic alterations with endoscopic or histological polyp characteristics were observed for BRAF, KRAS, TCF7L2, FBXW7 and CTNNB1 mutations. Multivariate analysis revealed that polyps ≥ 10 mm have a significant higher relative risk for harbouring oncogene mutations (relative risk 3.467 (1.742–6.933)). Adenomas and right‐sided polyps are independent risk factors for CTNNB1 mutations (relative risk 18.559 (2.371–145.245) and 12.987 (1.637–100.00)). Conclusions: Assessment of the mutational landscape of polyps can be integrated in the workflow of current colonoscopy practice. There are distinct genetic patterns related to polyp size and location. These results suffice to optimise individual risk calculation and may help to better define surveillance intervals.